Model of Zakat Community Development Program on Mustahik's welfare through Sustainable Development Goals Approach - Sugianto Sugianto; Mulia Anggi Wulandari; Ade Faizin; Aprielle Ego Pasha; R. Fakhrurrazi (International Journal of Management Research and Economics, 2025)
Zakat Community Development program is an initiative of the National Amil Zakat Agency (BAZNAS) which aims to empower mustahik through an integrative village-based community approach. This research aims to analyze the implementation of zakat management model based on Zakat Community Development program, assess the impact of ZCD program on mustahik economic growth and examine the synchronization of ZCD program with the achievement of sustainable development goals (SDGs). The author uses literature study and analysis of field findings from various ZCD implementation areas through Google Scholar and Publish or Perish application to assess the quality of sources, as well as analyzing data with content analysis techniques from various relevant articles and reports. The results show that; First, the Zakat Community Development model has been implemented by BAZNAS through community-based, multi-stakeholder collaboration, multi-sector integration, and mentoring and supervision. Second, the Zakat Community Development (ZCD) program has a positive impact on the economic growth of mustahik, through Da'wah, economic, education, health, and humanitarian programs. Third, the ZCD program has conceptual meeting points with several SDGs goals, such as SDGs 1, SDGs 2 and 11, SDGs 3, SDGs 4, and SDGs 16. This means that the integration of ZCD and SDGs can strengthen the role of zakat as a strategic solution in the economic and social development of mustahik.